A bibliometric study on culture research in international business - Pinto, Cláudia Frias (2021)
National cultures and cultural differences provide a crucial component of the international business (IB) research context. We conducted a bibliometric study of articles published in seven leading IB journals over a period of three decades to analyze how national culture has been impacting IB research. Co-citation mappings permit us to identify the ties binding works dealing with culture and cultural issues in IB. We identify two main clusters of research, each comprising two sub-clusters, with Hofstede’s (1980) work delineating much of the conceptual and empirical approach to culture-related studies. One main cluster entails works on the conceptualization of culture and its dimensions and the other cluster focuses on cultural distance. This conceptual framework captures the extant IB research incorporating culture-related concepts and influences.